International humanitarian law - Crawford, Emily (Writer on international law); Pert, Alison (Cambridge University Press, 2022)
"Emily Crawford is a lecturer and Director of the Sydney Centre for International Law (SCIL). She teaches international law and international humanitarian law, and has delivered lectures both locally and overseas on international humanitarian law issues, including the training of military personnel"--